EFEKTIVITAS MODEL PBL BERBANTUAN MEDIA PhET TERHADAP PROSES DAN HASIL BELAJAR SISWA - Marianus Marianus; Sixtus Iwan Umboh (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2020)
This study aims to determine the effectiveness of the PhET (Physics Education Technology) Simulation model of Problem Based Learning on the process and student learning outcomes in the Parabolic Motion material of Class X IPA of SMA Negeri 1 Remboken. This study was an experimental study with a population of Grade X students of Natural Sciences at SMA Negeri 1 Remboken, and a sample of 25 students was taken, with a pre-experimental one-groub pretest- posttest design. Data were analyzed from the results of the posttest, as well as from the assessment of science process skills and affective assessment criteria both 66% -79% and very good 80% - 100%. In the hypothesis test obtained tcount> ttable then H1 is accepted and H0 is rejected, meaning the average student learning outcomes using the Problem Based Learning model assisted by PhET simulation media is greater than the KKM. Based on the data obtained an average posttest score of 80.24 while the KKM determined from the school is 75. So it can be concluded that the Problem Based Learning model, assisted by PhET (Physics Education Technology) simulation media is effective on the process and learning outcomes of student physics.